Dimensional reduction in digital synthesizers GUI using parameter analysis (2011)
Digital synthesizers have cognitive overload issues for interaction, specially for novice or intermediate users. A system is developed to generate a custom GUI based on timbre clustering and parameter data analysis of preset programs present in VST synthesizers. The result is a new interface with dynamic control of the amount of variables maintaining full functionality of synthesizer performance. This system is designed to adapt to the degree of knowledge and cognitive control of synthesizer parameters of the user. The results of using diverse clustering techniques for synthesizers sound analysis and an original statistical analysis of preset programs parameter data are exposed. Implications of the use of our system in real world scenarios and reviewed.